Kepastian Hukum Atas Fatwa DSN-MUI Pada Bidang Perbankan Syariah Pasca Putusan Mahkamah Konstitusi Nomor 65/PUU-XIX/2021 - Arum Tarina; Muhammad Luthfi Radian; Meri Andriani (Jurnal Hukum Sasana, 2023)
Abstract: The background of this research is the Constitutional Court decision Number 65/PUU-XIX/2021, which review the Sharia Banking Law related to the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and Sharia banking regulations in Indonesia. From this decision the author analyzes it by applying Gustav Radbruch's concept of law, namely legal certainty. This research will use a normative juridical approach. Whereas the DSN-MUI Fatwa is not a positive law but rather a doctrine, which is called a source of law in a material sense. Given the principles and position of Islamic banking, which has specificity compared to conventional banking, namely applying Sharia principles, in which the DSN-MUI is involved. In order to guarantee legal certainty for stakeholders, the involvement of the DSN-MUI does not contain any legal issues at all as long as it is limited to issuing fatwas related to sharia principles, which are their authority. In this case, the state takes on the role of adopting sharia principles that have been stipulated by the DSN-MUI to become positive law that is enforced in the administration of state affairs in the field of sharia banking. Whereas this is in line with Radburch's opinion where normativity has legal certainty, factual matters that develop in the banking world can be studied and supervised first by the DSN-MUI before finally entering the juridical stage by mentaqninkan (making positive law) the DSN-MUI Fatwa as outlined in the form of PBI and/or POJK.